Citizens without political rights: A severed citizenship? (2014)
On December 9, 2013, the Attorney General's Office announced that it had imposed Mr. Gustavo Petro Urrego, Bogotá Mayor, the sanction of removal from office and general inability for the term of 15 years to hold public office. This decision generated public pronouncements and numerous actions for the protection of the violated rights. While the emphasis has been, in this case, on the collective dimension of political rights the article is interested in the individual dimension of the Law. The article seeks to show, from a recovery of the notion of citizenship, two issues. On the one hand, it shows that today deprivation of political rights is equivalent to a radical denial of the citizenship status and thus to the condition of equal in a political community of people who are recognized as equal in terms of rights. And, on the other hand, that the case of Gustavo Petro Urrego puts in the public sphere a new sensibility on the meaning of political rights, showing that their appropriation goes beyond the law.